Analysis of students’ motivation in participating in volleyball extracurricular activities - Utama, Sigit Widya; Kusumawardhana, Buyung; Wiyanto, Agus; Siregar, M. Jamaluddin (Sriwijaya Journal of Sport, 2026)
Research Problems: Volleyball is one of the extracurricular activities that is very popular among students at SMAN 10 Semarang. The existence of volleyball extracurricular activities at SMAN 10 Semarang must be accompanied by strong motivation in everyone. The results of observations showed that students who are members of the volleyball extracurricular at SMAN 10 Semarang do not show consistency. This raises the suspicion that there are differences in motivation that underlie students' participation in these activities. Research Objectives: This study aims to determine the level of intrinsic and extarinsic motivation of students in volleyball extracurricular activities at SMAN 10 Semarang. Methods: The approach used is descriptive quantitative, with data collection through questionnaires to describe the overall level of student motivation. Results: The results of the study show that the overall motivation of students at SMAN 10 Semarang who participated in volleyball extracurricular activities, as many as 20 students (66.7%) are in the high category of motivation to participate in volleyball extracurricular activities. The category of intrinsic motivation of students participating in volleyball extracurricular activities at SMAN 10 Semarang can be categorized as high (50.0%), and the extrinsic motivation of students participating in volleyball extracurricular activities at SMAN 10 Semarang is in the high category (80.0%). Conclusion: The results of the study show that the intrinsic and extrinsic motivation of students at SMAN 10 Semarang are all in the high category of motivation. Therefore, it can be concluded that students' desire to participate in volleyball extracurricular activities at SMAN 10 Semarang arises because of a combination of their own desires and support from a complementary environment.